Oxidative damage and myofiber degeneration in the gastrocnemius of patients with peripheral arterial disease - Weiss, Dustin J (BioMed Central, 2013)
Peripheral arterial disease (PAD), a manifestation of systemic atherosclerosis that produces blockages in arteries supplying the legs, affects an estimated 27 million people in Europe and North America. Increased production of reactive oxygen species by dysfunctional mitochondria in leg muscles of PAD patients is viewed as a key mechanism of initiation and progression of the disease. Previous studies demonstrated increased oxidative damage in homogenates of biopsy specimens from PAD gastrocnemius compared to controls, but did not address myofiber-specific damage. In this study, we investigated oxidative damage to myofibers as a possible cause of the myopathy of PAD. To achieve this, we developed and validated fluorescence microscopy procedures for quantitative analysis of carbonyl groups and 4-hydroxy-2-nonenal (HNE) adducts in myofibers of biopsy specimens from human gastrocnemius. PAD and control specimens were evaluated for differences in 1) myofiber content of these two forms of oxidative damage and 2) myofiber cross-sectional area. Furthermore, oxidative damage to PAD myofibers was tested for associations with clinical stage of disease, degree of ischemia in the affected leg, and myofiber cross-sectional area. Carbonyl groups and HNE adducts were increased 30% (p < 0.0001) and 40% (p < 0.0001), respectively, in the myofibers of PAD (N = 34) compared to control (N = 21) patients. Mean cross-sectional area of PAD myofibers was reduced 29.3% compared to controls (p < 0.0003). Both forms of oxidative damage increased with clinical stage of disease, blood flow limitation in the ischemic leg, and reduced myofiber cross-sectional area. The data establish oxidative damage to myofibers as a possible cause of PAD myopathy.